Novel urinary and serological markers of prostate cancer using proteomics techniques: an important tool for early cancer diagnosis and treatment monitoring - Adeola, Henry Ademola (Division of Medical Biochemistry, 2016)
In Africa, Prostate cancer (PCa) is the most frequently diagnosed solid organ tumour in males and use of prostate specific antigen (PSA) is presently fraught with diagnostic inaccuracies. Not least, in a multi-ethnic society like South Africa, proteome differences between African, Caucasian and Mixed-Ancestry PCa patients are largely unknown. Hence, discovery and validation of affordable, non-invasive and reliable diagnostic biomarkers of PCa would expand the frontiers of PCa management. We have employed two high-throughput proteomics technologies to identify novel urine- and blood-based biomarkers for early diagnosis and treatment monitoring of prostate cancer in a South African cohort as well as elucidate proteome differences in patients from our heterogeneous cohort. We compared the urinary proteomes of PCa, Benign Prostatic Hyperplasia (BPH), disease controls comprising patients with other uropathies (DC) and normal healthy controls (NC) both by pooling and individual discovery shotgun proteomic assessment on a nano-Liquid chromatography (nLC) coupled Hybrid Quadrupole-Orbitrap Mass Spectrometer platform. In-silico verification of identified biomarkers was performed using the Human Protein Atlas (HPA) as well as SRMAtlas; and verified potential biomarkers were experimentally prevalidated using a targeted parallel reaction monitoring (PRM) proteomics approach. Further, we employed the CT100+ antigen microarray platform to assess the differential humoral antibody response of PCa, DC and BPH patients in our cohort to a panel of 123 tumour-associated cancer antigens. Candidate antigen biomarkers were analyzed for ethnic group variation in our cohort and potential cancer diagnostic and immunotherapeutic inferences were drawn. Using these approaches, we identified 5595 and 9991 non-redundant peptides from the pooled and individual experiments respectively. While nine proteins demonstrated ethnic trend, 37 and 73 proteins were differentially expressed by pooled and individual analysis respectively. All 32 verified biomarkers were prevalidated with parallel reaction monitoring. Good PRM signals for 12 top ranking biomarker was observed, including PSA and prostatic acid phosphatase. We also identified 41 potential diagnostic and immunotherapeutic antigen biomarkers. Proteogenomic functional pathway analyses of differentially expressed antigens showed similar enrichments of biologic processes. We identified herein novel urinary and blood-based potential diagnostic biomarkers and immunotherapeutic targets of PCa in a South African PCa Cohort using multiple proteomics approaches.